An Investigation of Anticholinesterase and Anticancer Effects of Verbascum insulare Boiss. Et Heldr. Extracts Growing in Muş Region - Alan, Yusuf; Almaz, Züleyha (My University, 2022)
Since the existence of humanity, plants have been used in many treatment methods. Members of the genus Verbascum, a member of the Scrophulariaceae family, also known as mullein, have recently received great attention due to their remarkable biological activities and have been evaluated in traditional therapeutic uses against various ailments. In this study, the anticholinesterase and anticancer activities of Verbascum member Verbascum insulare Boiss. Et Heldr. collected from Muş region were investigated. V.insulare leaf ethanol (L-EtOH), leaf purified water (L-PW), root ethanol (R-EtOH), and root purified water (R-PW) extracts were obtained. The anticancer activity of the extracts against HT-29, MCF-7, and L-929 cell lines was examined using the 3-(4,5-dimethyl-thiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) test, and the anticholinesterase activity of the extracts was determined. It was found that the ethanol extract showed higher anticancer activity against cancer cell lines than the pure water extract and had more effective anticholinergic influences. It is aimed to shed light on the biological effects of Verbascum insulare Boiss. Et Heldr, which is thought to be a natural source of bioactive compounds for the development of phytopharmaceuticals targeting oxidative stress-related diseases such as cancer and neurological diseases. No study has been found in the literature on the anticancer and anticholinesterase activity of this plant yet. Therefore, the results obtained from this study will contribute significantly to the development of herbal medicine in the future.